Klasifikasi Penyakit Ginjal Kronis Menggunakan K-Nearest Neighbors dengan Feature selection Pearson Correlation Coefficient - Khadiki, Mohammad Rizan; Fitria, Vivi Aida (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Chronic kidney disease (CKD) is a global health issue that impacts quality of life and mortality rates. CKD often shows no symptoms in its early stages, earning it the nickname